Measuring procurement performance of LGED and RHD based on key performance indicators (KPIs) - Kamruzzaman, Abu Sayed Md. (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.